Longitudinal Associations of Self-Reported Visual, Hearing, and Dual Sensory Difficulties With Symptoms of Depression Among Older Adults in the United States - Killeen, Olivia J.; Xiang, Xiaoling; Powell, Danielle; Reed, Nicholas S.; Deal, Jennifer A.; Swenor, Bonnielin K.; Ehrlich, Joshua R. (Frontiers in Neuroscience, 2022)
Evidence conflicts on the association between sensory difficulty and depression. Few studies have examined this association using longitudinal or population-based data. We used data from Rounds 1–9 of the nationally representative National Health and Aging Trends Study to evaluate the longitudinal association between self-reported visual, hearing, and dual sensory difficulties and clinically significant depressive symptoms. Multivariable Cox regression models were used to evaluate the hazard of incident depressive symptoms. Group-based trajectory modeling identified depressive symptom trajectories (DSTs). Multinomial logistic regression was used to examine the association between sensory status and DSTs. A total of 7,593 participants were included: 56.5% were female, 53.0% were 65–74 years old, 19.0% (95% CI 17.9–20.2%) had hearing, 5.6% (4.9–6.4%) had visual, and 3.3% (2.9–3.8%) had dual sensory difficulties at baseline. Hazard ratios for depressive symptoms in those with visual, hearing, and dual sensory difficulties were 1.25 (95% CI 1.00–1.56, p = 0.047), 0.98 (95% CI 0.82–1.18, p = 0.82), and 1.67 (95% CI 1.29–2.16, p < 0.001), respectively, relative to those without sensory difficulty. A model with four trajectory groups best fit the data. Group 1 (35.8% of the sample, 95% CI: 34.1–37.4) had persistently low risk of depressive symptoms; Group 2 (44.8%, 43.4–46.3) had low but increasing risk; Group 3 (7.1%, 6.2–8.3) had moderate risk; and Group 4 (12.4%, 11.5–13.3) had moderate to high risk that increased. Compared to those without sensory difficulties, individuals with each difficulty were significantly more likely to belong to a group other than Group 1. This study reveals associations between sensory difficulties and mental health that can inform public health interventions.